Revolutionizing women’s health care with a sustainable change: Breast Green Surgery (BuGS) protocol - G. Vanni; M. Materazzo; S. Chemello; M. Pellicciaro; V. Marsella; F. Calenda; D. Eskiu; G. Lisi; G. Pistilli; S. Bastone; B. Longo; V. Cervelli; et al. (World Cancer Research Journal, 2024)
Objective: Breast Cancer (BC) is the primary oncological diagnosis in women, with the annual incidence expected to exceed 3 million new cases by 2040 due to population growth and ageing. During the COVID-19 pandemic, novel methods were adopted to provide continuous care to patients, including the introduction of telehealth. This technique allows for improved access to care, reduced emissions with environmental impact, better resource utilization, and ultimately improved continuity of care. A current issue is the environmental impact of hospitals, particularly operating rooms, as it has been analyzed that 25-30% of hospital waste comes from these areas. In this regard, there has been a consideration to introduce the ERAS protocol, already active in colorectal surgery, into breast surgery, aiming to optimize resources, reduce hospital waste, and expedite waiting lists.